Comportamento sedentário na pessoa idosa após a alta hospitalar - Barbosa, Jéssica Fernanda (Universidade Federal de São Carlos, 2025)
Acute events such as hospitalizations negatively impact the health of older adults. Sedentary behavior (SB) may not only increase the likelihood of hospital readmission but also contribute to the development of hospitalization-associated disability. However, it remains unclear whether SB is also associated with the functional and physical capacity of older patients after hospital discharge. Objective: To analyze the time spent in SB and its patterns in older adults after hospital discharge and to evaluate the association between SB and functional and physical capacity one month after discharge. Methods: This longitudinal study included 60 older adults assessed at discharge from the UFSCar University Hospital and one month after discharge. SB was measured using the ActivPAL3™ micro accelerometer, and data were processed with PALanalysis software to calculate the average total time in SB (sitting + lying awake), the percentage of time in SB (%SB), and prolonged bouts of 30 and 60 minutes over five valid days. Physical capacity was assessed using the Timed Up and Go (TUG) test, handgrip strength (HGS), and the Short Physical Performance Battery (SPPB). Functional capacity was evaluated using the Barthel Index. Paired T-tests were used for parametric data, and Wilcoxon tests for non-parametric data to compare physical and functional capacity and SB metrics between hospital discharge and one month later. Pearson and Spearman correlation coefficients were used for parametric and non-parametric data, respectively. Statistical analyses were conducted using JAMOVI software (version 2.3.18), with significance set at p < 0.05. Results: The mean age of the sample was 74 ± 9.26 years, and 61% were female. Improvements were observed in physical capacity (TUG: 20.2 s to 14.5 s; HGS: 22 kgf to 24 kgf; SPPB: 7 points to 9 points) and functional capacity (Barthel Index: 90 points to 100 points) one month after discharge, along with reductions in SB, %SB, and 60-minute bouts (11.38 to 9.86 hours, 75.8% to 65.3%, and 1.68 to 1.34 bouts, respectively). %SB and prolonged bouts were associated with poorer physical capacity one month after discharge. Conclusion: The findings of this study are expected to inform future discharge planning aimed at reducing SB and modifying its patterns following hospitalization.
Sedentary behavior in older adults after hospital discharge
Keywords: Idosos; Alta hospitalar; Comportamento sedentário; Capacidade Física; Capacidade funcional; Older adults; Hospital discharge; Sedentary behavior; Physical capacity; Functional capacity; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL